The ten-syllable Portuguese verse - José Américo Miranda; Rilane Teles de Souza (Texto Poético, 2018)
This paper examines the ten-syllable verse in some treatises of versification in Portuguese language, from the eighteenth century to the second half of the twentieth century. Since Renaissance, the Italian ten-syllable verse predominated in Portuguese poetry. In the succeeding centuries, the treatises of versification made it a practically unique recipe for this verse. In Symbolism and Modernism, by the recovery of rhythmic schemes used in the Middle Ages and by the use of other possibilities little used in the past, this verse was decristalized, recovered the enormous plasticity it had once. A sample of contemporary poetry, presented at the end of the paper, surpasses modernist ruptures.